Machine learning for remote proctoring - Zhang, Zhenghang (Nanyang Technological University, 2022)
Due to the COVID-19 epidemic, an increasing number of schools and organizations have been forced to conduct online tests in recent years. While online examinations are convenient for users and successful in preventing the spread of the virus, they lack a robust proctoring system when compared to traditional offline exams. Many existing online tests are completely monitored by humans, which means the proctors must watch all of the users’ actions on the screen, which is simply inefficient and time-consuming.